PENGARUH LOKASI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA KOPI JANJI JIWA Institut Bisnis dan Komunikasi Swadaya (SWINS) - Mulyadi; Marthen Asa (Ekonomi Digital, 2025)
The Influence of Location and Service Quality on Consumer Satisfaction at Kopi Janji Jiwa. The location of the cafe is an important element that influences how easily customers can visit the cafe. The quality of coffee and food products served in cafes including taste, freshness and menu variety are also significant factors in shaping customer perceptions. The aim of this research is to determine the quality of service on consumer satisfaction at Janji Jiwa coffee. Does service quality influence visitors to Janji Jiwa coffee? This type of research uses a quantitative approach with survey methods. Survey research is research that takes samples from a population and uses questionnaires as a data collection tool. This research was conducted at Jalan Perintis Independen Apartment Oak Apartments. No. Kav. 99 RT/RW 1/1 Pulo Gadung Kec. Pulo Gadung, East Jakarta City, Jakarta Capital City 13260 (1) Location has a significant and positive effect on consumer satisfaction with Kopi Janji Jiwa. (2) Service quality has a significant and positive influence on consumer satisfaction with Kopi Janji Jiwa. (3) Location and service quality simultaneously (together) have a significant effect on consumer satisfaction with Kopi Janji Jiwa. Based on the results of the analysis and testing of the third hypothesis (H3) using the F test (simultaneous) it was found that location and service quality simultaneously (together) had a significant effect on consumer satisfaction with Kopi Janji Jiwa. Multiple linear regression analysis also produces values R Square (R2) of 0.547, which means that the contribution of the influence of location variables and service quality to consumer satisfaction at Kopi Janji Jiwa is 54.7% and the remaining 0.453 (45.3%) is influenced by other variables not studied, such as: price, product quality, the quality of human resources, in this case the abilities/skills of the officers at Kopi Janji Jiwa, and so on. An influence contribution above 50% shows quite a large influence, this indicates that the location and quality of service have quite a large impact on consumer satisfaction, especially for visitors to Kopi Janji Jiwa.